Two new diminutive species of Begonia (Begoniaceae) from the north coast of São Paulo State, Brazil - Miranda, Marcelo Dias; Jacques, Eliane De Lima (Phytotaxa, 2022)
Two new species of Begonia (Begoniaceae) from the Atlantic Coastal Forest of Brazil are described and illustrated. Begonia atlantica and Begonia umbrosa are found living in rocky outcrops present on the slopes of Serra do Mar State Park, taxonomic affinities and provisional conservation assessments are also provided.